Educação Inclusiva e jogos de cartas: o Jogo Acolher como proposta facilitadora do processo de inclusão de pessoas com deficiência no Ensino Superior - ASSUNÇÃO, Paulo Andrey Loredo de (Universidade Federal do Pará, 2024)
The aim of this research was to develop a card game aimed at higher education students, which would help to reduce attitudinal barriers and contribute to the inclusion of people with disabilities (PwD) at this level of education. It was carried out using a qualitative approach, which guided the exploratory and field research. The theoretical basis was provided by studies involving Inclusive Education, such as Oliveira, I. (2002, 2017); Lima, S. (2017); Gamification and Games such as Kapp (2012); Gomes (2015, 2019) and Busarello (2016), in addition to documents from international conventions and Brazilian legislation regarding guidelines and orientations on the teaching of PwD, such as the Salamanca Declaration and the Brazilian Law for the Inclusion of People with Disabilities Law No. 13.146/15, respectively. The field research unfolded from internships and experiences at the Dentistry Course at the Federal University of Pará (UFPA) and at the institution's Accessibility Coordination Office (CoAcess), with monitoring in each of the five divisions that provide support for students with disabilities. The active methodology called Gamification was used to develop the product. The product validation process was supported by a semi-structured questionnaire answered by course students and a panel of experts via Google Forms. The results from the students' point of view indicate that the game meets the proposed objectives and arouses interest in the subject, while the experts believe that the product can generate curiosity about the subject and contribute to reflection and a change in attitude. Thus, it is understood that even though the final version of the game is presented, it is not limited to a single version, situation or form of gameplay, but provides and invites the challenge of different practices in the teaching context to which it is directed.